Hacia algunas inteligibilidades en la administración. Propuestas metodológicas para aproximarse al discurso administrativo (2019)
Contextualizing management knowledge implies the development of fluid intelligences that enable professional managers to give sense to polyvalent meanings, pragmatically orient her/his knowledge and solidly ground her/his understandings. Discourse analysis, story telling and interpretation, and critical thinking are proposed as study areas that enhance the intelligibility of administrative theory and deeds. Besides constituting relevant research objectives for several contexts, such methods can be mixed with service experiences and attitude that bridges the gap between management theories and actual practices, while forging new interpretations of reality, founded in solid epistemological criteria.